Optimizing the spatial accessibility of public green spaces in high-density communities in Macau under an all-age orientation - Wang, Yifan; Wang, Pohsun; Zhou, Junling (Frontiers in Built Environment, 2025)
IntroductionAs one of the cities with the highest population density in the world, Macau has long faced the issues of insufficient public green spaces and uneven spatial distribution. This study focuses on 18 public green spaces in the Youhan and Taishan communities, where the population density exceeds 104,000 people per square kilometer.MethodsUtilizing road and green spaces data released by the IAM (INSTITUTO PARA OS ASSUNTOS MUNICIPAIS) and field research results, a spatial model was constructed in AutoCAD. Multi-scale spatial syntax indicators, including global integration, local integration (r = 3), synergy (n = 200 and n = 400), and selection, were calculated through Depthmap Beta 1.0.ResultsThe results indicate that the average global integration of the street network is 1607.97, while the average for public green spaces is 1976, with a maximum of 2770.4 and a minimum of 1134.08, showing significant regional differences. The synergy coefficient of the street network reaches 0.93–0.99, indicating a high degree of consistency between local and overall structures. However, some small green spaces have low utilization rates due to their single function, insufficient connectivity, and lack of age-friendly facilities.DiscussionAddressing these mismatch issues, this article proposes optimization strategies based on the “agefriendly” concept and maps them to the eight dimensions outlined in the World Health Organization (WHO) (2007) “Global Age-Friendly Cities:” spatial friendly strategies correspond to outdoor spaces, buildings, and transportation systems; service-friendly strategies emphasize multifunctionality and health support facilities; policy support strategies highlight inclusivity, citizen participation, and governance transparency. By combining quantified spatial accessibility indicators with the internationally recognized age-friendly framework, this study provides a robust and scalable approach for equity-oriented green space planning in Macau and other high-density cities.